A laser-induced dual ultrasonic wave method for noncontact load monitoring of pillar porcelain insulators. (1st March 2023) - Zhao, Zhou-Feng; Feng, Qian; Hui, Yang; Lu, Kuang-Da; Li, Xiao-Ying; Ye, Bo; Zhang, Jun; Song, Tao
Abstract: In this paper, a noncontact load monitoring method based on laser-induced synchronous ultrasonic surface wave and air wave is presented to improve the accuracy of load measurement on pillar porcelain insulator. In order to eliminate the measurement error caused by insulator deformation, a correction algorithm for surface wave velocity calculation is established by introducing the air wave propagation time. An experimental setup of the load measurement system for pillar porcelain insulators based on laser-induced dual ultrasonic waves was assembled. A load calibration experiment and load detection experiment were carried out under various bending and torsional loads. The results showed that the proposed method is effective to solve the problem of the surface wave propagation time changing abruptly, greatly increasing the accuracy of load measurement. In the monitoring experiments, the relative error between the calculated load value and the actual applied load value was small, the average measurement error of the bending load was 16.20%, and the average measurement error of the torsional load was 11.38%. This proved that the measurement of the insulator load value using a laser ultrasonic surface wave is more precise than the traditional methods, making it more suitable for engineering inspection.